A network visualization approach and global stock market integration. (5th March 2018) - Tong, Chen; Chen, Jing; Buckle, Mike J.
Abstract: This paper applies a visualized network approach to analyse the degree of integration or comovement among global equity markets. We utilize daily prices of stock market indices of 57 countries from January 1997 to August 2012 to establish both a minimum spanning tree network and graph network. We examine network features including connectivity and centrality through a variety of indicators. Our results clearly show that there has been a tendency over time for markets to become more integrated globally even during periods of market stress. The centrality results suggest that the U.S. and Hong Kong markets have been the most dominant markets in their geographic region. For Europe, we find 3 dominant centres, the United Kingdom, France, and Germany in contrast to previous literature suggesting that the United Kingdom was the dominant country. We further identify that Japan and Australia, instead of acting as dominant countries in their region, serve as bridging countries between the region and the rest of the world. Finally, we find that Africa does not form a cluster, and individual African countries tend to connect to other developed markets.